Feasibility evaluation of multi–site scheduling by distributed simulation of workshops. (9th January 2012) - Enjalbert, S.; Archimè, B.; de,
In this paper, a distributed simulation tool for the feasibility evaluation of multi–site scheduling is proposed. The application areas concern Supply Chains (SCs) or networks of cooperating and distributed workshops. To facilitate the modelling of a corporate network, a generic framework is proposed. The distributed simulation of workshops, called virtual workshops, generates various problems of causality and of tasks execution coordination. These problems are addressed in the proposed distributed architecture by the use of High Level Architecture (HLA) protocol guaranteeing the synchronisation and the chronology of events. An application to a simple case of SC organising the flow between three workshops shows the effectiveness of the distributed simulation tool.